The Toy's Party for pre-primary - "Hunt, Roderick" (Oxford University press)
The Toy's Party" by Roderick Hunt is a delightful children's story featuring characters from the popular Oxford Reading Tree series. In this tale, a group of toys comes to life and decides to throw a party. Each toy has its own personality and contributions, leading to a fun and chaotic celebration. Throughout the story, themes of friendship, creativity, and the joy of play are explored, as the toys navigate their challenges and work together to make the party a success. The vibrant illustrations and engaging narrative make it an enjoyable read for young children.
Keywords: Textbook